Lactic dehydrogenase as a biochemical marker of adverse pregnancy outcome in severe pre-eclampsia, Gujarat - Jain, Rohit; Upadhyay, Chintan; Mehta, Latika; Nayak, Bipin; Desai, Gaurav (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Serum LDH levels can be used to assess the extent of cellular death and thereby the severity of disease in this group of women. This will help in making decision, about the management guidelines to the better the maternal and fetal outcome. Objective of present study was compare serum LDH levels in the normal pregnant women and in women with preeclampsia and eclampsia in ante-partum period and to study the association of maternal and perinatal outcomes with serum LDH levels. Methods: It is a prospective study done at Obstetrics and Gynecology department, GMERS medical college and civil hospital, Gandhinagar during August-September 2016. Participants were divided into four groups according to severity of disease and into three groups according to serum LDH level. Results: Mean level of LDH (IU/l) in Control, Mild pre-eclampsia, Severe pre-eclampsia & Eclampsia was 302.33, 398.56, 675.26 & 1589.85 respectively. Out of total 34 cases with LDH level >800 IU/L, 47.1% cases had ≥160 mm hg SBP & 52.9% had ≥110 mm hg DBP, mean gestational age and mean baby weight was 36.88 week and 1950 gm, mean apgar score at 10 min was 6.96, 47.1% had uneventful outcome, whereas 58.8% had neonatal complications and 5.9% had neonatal death. Almost 26.5% still births, 47.1% perinatal deaths. Conclusions: Higher serum LDH levels during pregnancy have significant association with severity of disease and maternal and fetal outcomes in patients of preeclampsia and eclampsia and can be considered as a supportive prognostic tool from early third trimester.